2010
DOI: 10.1016/j.ssc.2010.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous magnetic behavior of CuO nanoparticles

Abstract: We report studies on temperature, field and time dependence of magnetization on cupric oxide nanoparticles of sizes 9 nm, 13 nm and 16 nm. The nanoparticles show unusual features in comparison to other antiferromagnetic nanoparticle systems. The field cooled (FC) and zero field cooled (ZFC) magnetization curves bifurcate well above the Néel temperature and the usual peak in the ZFC magnetization curve is absent. The system does not show any memory effects which is in sharp contrast to the usual behavior shown … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 47 publications
5
19
0
Order By: Relevance
“…[50][51][52][53][54] The ZFC data show a peak, and the peak broadens and shifts to low temperatures on increasing the magnetic field. We analysed the nature of this peak and found that the peak temperature (T P ) as a function of field (H) does not behave as in the case of spin-glasses, cluster-glasses, 55 or superparamagnets 56,57 which indicates that the system is neither a spin-glass nor a superparamagnet. We also rule out supercooling as a possible reason for the FC-ZFC irreversibility by the following argument.…”
Section: The Fc-zfc Irreversibilitymentioning
confidence: 99%
“…[50][51][52][53][54] The ZFC data show a peak, and the peak broadens and shifts to low temperatures on increasing the magnetic field. We analysed the nature of this peak and found that the peak temperature (T P ) as a function of field (H) does not behave as in the case of spin-glasses, cluster-glasses, 55 or superparamagnets 56,57 which indicates that the system is neither a spin-glass nor a superparamagnet. We also rule out supercooling as a possible reason for the FC-ZFC irreversibility by the following argument.…”
Section: The Fc-zfc Irreversibilitymentioning
confidence: 99%
“…5,6 EB has been explained in terms of interaction between an AFM core and a spin glass-like or FM shell of uncompensated surface spins. 7,9,11 EB has also been observed in CuO nanowires 13 and nanostructures. 14 Differences might appear when determining the ordering temperature in nanostructured CuO based only on magnetic measurements.…”
Section: Introductionmentioning
confidence: 82%
“…Indeed, it shows a change of slope at T N and a broad maximum near 550 K 2 which has been explained in terms of a strong linear chain antiferromagnetism, along [1 0 1] direction. 3,4 CuO nanoparticles exhibit atypical properties, such as ferromagnetic (FM) response at room temperature (RT), [5][6][7][8] exchange bias (EB) phenomenon, [9][10][11][12] and variation of AFM order temperature. 9, 10 Several models have been designed to explain those findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, NiO nanoparticles have been reported to show spin glass like behavior; 6,12 CuO nanoparticles show an anomalous magnetic behavior that cannot be described as superparamagnetic or spin glass like; 22 Ferritin shows superparamagnetic behavior 8,23 etc. Co 3 O 4 is an antiferromagnetic material and in the bulk form, its Néel temperature has been reported to lie between 30 K and 40 K. 24 There have been some reports on hysteresis, time dependence of magnetization, exchange bias and finite size effects in bare, coated and dispersed Co 3 O 4 nanoparticles and various claims have been made in support of spin glass like and superparamagnetic behavior in these particles.…”
Section: 19-21mentioning
confidence: 99%